Effect of storage time and gamma irradiation on the chemical properties of olive (Olea europaea) oils - Al-Bachir M. (International Journal of Food Studies)
The objective of this study was to investigate the effects of gamma irradiation at doses of 0, 1, 2 and 3 kGy, and storage time of olive fruits for 0, 30 and 45 days on changes in chemical properties of olive oil during storage periods of 0, 6 and 12 months. The initial acidity value (AV), peroxide value (PV), Thiobarbituric Acid (TBA), phenolic content, iodine value (IV) and saponification value (SV) of virgin olive oil obtained from olives fruits immediately after harvest (at day zero) were 1.04%, 3.06 mEqO2 kg−1 oil, 0.025 mg MDA kg−1 oil, 314.71 mg gallic acid kg−1 oil, 93.38 gI2 100 g−1 oil and 194.88 mg KOH g−1 oil, respectively. In general, the AV and PV of olive oil was increased by gamma irradiation, while the phenolic and IV of olive oil was deceased by gamma irradiation and storage time. The TBA value and SV of olive oil was not significantly (p>0.05) changed by gamma irradiation.